Cognitive processes and academic achievement in EMR adolescents - Blackman, L S; Bilsky, L H; Mar, H (American journal of mental deficiency, 1976)
Twelve cognitive process variables were investigated as predictors of reading and arithmetic achievement and studied for internal structure, with 115 EMR adolescent subjects. Stepwise regression and factor analyses were employed to study prediction and structure, respectively. Memory variables were the most important predictors of reading. They were also involved in arithmetic but to a lesser extent. The data suggested that the ability to generate and utilize strategies facilitating the recall of unstructured material as well as the capacity to be sensitive to strategy-relevant structure embedded in stimuli were important prerequisites for the acquisition of reading skills. An oddity task, measuring the ability to maintain the same relational focus for successive applications to new stimulus material, was found to be most pertinent for predicting arithmetic computational skills.